207k views
1 vote
If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (fx g)(x)?

(3x + 2)(x^2 + 1)
3x^2 + 1 + 2
(3x + 2)2 + 1
3(x 2 + 1) + 2

1 Answer

2 votes

Answer:


(3x + 2)( {x}^(2) + 1)

Explanation:

The given functions are


f(x) = 3x + 2

and


g(x) = {x}^(2) + 1

By the algebraic properties of functions:


(f * g)(x) = f(x) * g(x)

We just have to substitute to obtain:


(f * g)(x) =(3x + 2)( {x}^(2) + 1)

The first choice is correct.

User Michael Cordingley
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.